Unusual presentation of breast lump-diagnosed on FNAC as tubercular lesion - Sengupta, S; Mondal, RK; Ray, R; Bose, K; Ghosh, TK (Nepal Journal of Medical Sciences, 2013)
Tuberculosis of breast is a rare disease even in endemic areas accounting for 0.1%- 0.5% of all infections. Multiparous young females are commonly affected particularly during pregnancy and lactation. In the present study, we are reporting a case of tuberculosis of breast with ipsilateral axillary involvement in a multiparous young non lactating female. Diagnosis was confirmed after cytological evaluation. Clinical or radiological distinction of mammary tuberculosis from breast carcinoma or abscess is often difficult to achieve. Cytology is an effective method for confirmation of these uncommon disorder an also can reduce unnecessary surgery which should be restricted for complicated cases. Nepal Journal of Medical Sciences | Volume 02 | Number 02 | July-December 2013 | Page 187-189 DOI: http://dx.doi.org/10.3126/njms.v2i2.8974